Happily Ever After? Story Endings in Hebrew Children's Literature. Issue 1 (2nd July 2020) - Rudin, Shai
ABSTRACT: This study examined the assumption that children's stories conclude with a happy End and found five different types of Ends in Hebrew children's literature: the happy End, the happy-enough End, the ambivalent End, the open End, and the bad End. In addition to the Bibliotherapeutic Approach whereby children should be exposed to realistic texts that do not enhance escapism, additional approaches also exist. The open, ambivalent, and bad Endings enable the emergence of more complex themes, together with multi-layered poetics, that challenge children's thinking and turn children's stories into a complex art medium rather than a didactic one.